Is chronic synovitis an example of reperfusion injury?. Issue 7 (July 1986) - Woodruff, T; Blake, D R; Freeman, J; Andrews, F J; Salt, P; Lunec, J
Abstract : In an attempt to define why the joint synovial cavity is prone to develop persistent synovial inflammation we show that hypoxia is induced by pressure changes caused by exercise in the presence of an inflammatory effusion. On resting 'reperfusion injury' may take place. The biochemistry of reperfusion injury has only recently been defined and perhaps surprisingly for an insult that has hypoxia as its central ingredient involves the subsequent production of oxygen derived free radical species. We apply the reaction sequences that are believed to occur during hypoxic/reperfusion injury to the joint synovial cavity and, on the basis of reported 'in vivo' observations, suggest novel therapeutic approaches that we believe are applicable to the treatment of persistent synovial inflammation.